Competency-Based Curriculum-The Panacea - Ernest, Joshua (Journal of Engineering Education Transformations, 1997)
With a result - demanding society, the industry has found out that the competency - based curriculum for their ill house training, as an excellent strategy - that learning being always observable and measurable. If this approach is adopted by the technical education, the passouts of which are the direct inputs to the industry, the lat er may co-operate much more as they will be the first to be benefited. They will get personnel with the requisite competencies who can be directly put on the job without any preliminary training. This will encourage an active partnership from the industry, right from the curriculum planning stage, also resulting in bringing about a lot of clarity in the instructional strategy and evaluation . This paper examines the concept of competency and argues the need for the technical education system to shift to the competency-based curriculum.